Analysis of the Effects of Land-Use Changes on Increased Flood Discharge in the Hetuma River Using a Hydrological Approach - Unas Tabuni; Mujiati; Bahtiar; Duha Awaluddin Kurniatullah; Bernathius Julison (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
Changes in land use due to residential expansion and infrastructure development have increased surface runoff, contributing to higher flood discharge in the Hetuma River, Jayawijaya Regency. This study aimed to analyze the impact of land-use changes on increased flood discharge and develop an optimization model for drainage systems to reduce inundation in Wamena City. The research employed a hydrological approach using the Nakayasu Synthetic Unit Hydrograph (Hidrograf Satuan Sintetis or HSS) method and the Rational Method. The data used included BMKG rainfall records from 2013–2024, topographic data, watershed maps, and land-cover maps from 2015 and 2025. The results showed that forest areas decreased from 217.70 ha to 139.39 ha, while residential areas increased from 177.67 ha to 183.17 ha. These land-use changes increased the runoff coefficient, which subsequently contributed to higher flood discharge. Based on the Nakayasu Synthetic Unit Hydrograph method, the design flood discharge of the Hetuma River reached 20.712 m³/s for the 2-year return period and 26.474 m³/s for the 100-year return period. Meanwhile, the Rational Method results indicated that flood discharge increased from 281.970 m³/s for the 2-year return period to 504.967 m³/s for the 100-year return period. Drainage analysis revealed that several channels in the Hom-Hom area were unable to accommodate runoff discharge due to sediment accumulation and limited channel capacity, requiring channel normalization and dimension improvements. Therefore, land-use changes were proven to contribute to increased flood discharge in the Hetuma River, highlighting the need for land-use management and drainage system optimization to reduce flood risks in Wamena City.